To find the equation Berta might have written in Step 1, we need to consider how she got to Step 2, where she found that \( x = -2 \).
The equation she used in Step 3, \( 4(-2) + y = -5 \), suggests that she substituted \( x = -2 \) back into one of the original equations to solve for \( y \).
Since she was clearly solving the system of equations composed of:
- \( 4x + y = -5 \)
- \( x - y = -5 \)
We need to focus on a potential equation for Step 1 that logically leads to finding \( x = -2 \).
We can express \( y \) in terms of \( x \) using the second equation:
- From \( x - y = -5 \), we can rearrange it to \( y = x + 5 \).
Substituting this expression for \( y \) back into the first equation: \[ 4x + (x + 5) = -5 \] Combine similar terms: \[ 4x + x + 5 = -5 \ 5x + 5 = -5 \ 5x = -10 \] This simplification gives us \( 5x = -10 \), indicating this could have been an equation Berta could have written in Step 1.
Now evaluating the options provided:
- \( 4x = 0 \)
- \( 5x = 10 \)
- \( 5x = -10 \) <-- This is the equation we derived.
- \( 5x = -25 \)
Thus, the equation Berta might have found in Step 1 is:
5x = -10.